A retrospective analysis on patients at high‐risk for obstructive sleep apnea undergoing ear, nose, and throat surgeries. Issue 1 (29th December 2017) - Woodling, Karina; Fiorda‐Diaz, Juan; Otto, Bradley A.; Barnes, Christie A.; Uribe, Alberto A.; Bergese, Sergio D.; Yildiz, Vedat; Stoicea, Nicoleta; Guertin, Michael G.
Abstract : Background: Obstructive sleep apnea (OSA) may be related to episodes of oxygen de‐saturation, hypercapnia, cardiovascular dysfunction, cor‐pulmonale, and pulmonary hypertension. STOP‐BANG is an acronym for eight specific questions used to assess the likelihood of OSA. If the individual exhibits three or more of these indicators, he/she should be considered to be at high risk for OSA complications. Therefore, the decision of proceeding with inpatient versus outpatient ENT surgery still remains controversial. The primary objective of the study was to identify and correlate desaturation (SPO2 <90%) episodes and risk factors. Methods: We conducted a single‐center retrospective study between October 1, 2011 and August 31, 2014 in order to identify postoperative complications during the first 24 hours that justify postoperative monitoring and hospital admission. A total of 292 subjects were included for data analysis. Patients were divided into two groups based on the number of OSA risk factors: group A with 3–4 risk factors (n = 166), and group B with ≥5 risk factors (n = 126). The following information was collected: demographics, ASA, preoperative STOP‐BANG score, length of surgery, intraoperative complications, opioid consumption, post anesthesia care unit (PACU) and overall length of stay, supplemental oxygen requirement, oxygen desaturation, and postoperative opioid consumption. Results: No statistically significant difference was found when comparing demographic variables between both groups. All STOP‐BANG variables showed statistical significance. PACU and inpatient variables were similar among both groups, with the exception of length of hospital stay (longer stay in group B when compared to group A [ p = 0.003]). Desaturation differences between both groups during PACU were statistically significant ( p = 0.008). A post‐hoc analysis showed a 0% incidence of overall desaturation in the group with three STOP‐BANG indicators. Conclusions: Our retrospective analysis concluded that patients diagnosed with three STOP‐BANG risk factors did not experience postoperative complications and hospital admission was not justified. Level of Evidence: 4